PERSPEKTIF KONSUMEN CITA RASA KULINER LOKAL TERHADAP PRODUK WARUNG BEBEK GORENG CABANG PURNAMA DI SURABAYA - Praseton Sepsi Winarno (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. One of the culinary businesses that is rampant in the city of Surabaya is fried duck. Considering that Surabaya is the second largest city in Indonesia after Jakarta. So that makes culinary businessmen take advantage of strategic places in this city. One of the culinary businesses in Surabaya that serves duck dishes is Bebek Purnama. This stall is located along the roadside of Surabaya, lots of stalls with the words